Comparison of efficacy rinsing with cocoa seed extract, green tea catechins extract and lime extract to salivary ph in children suffering ECC (Early Childhood Caries) - Fajriani Fajriani; Meilisa Yusriyanti (Journal of Dentomaxillofacial Science, 2018)
Objective: This study aims to determine whether 12.5% cocoa extract, green tea catechins 30% extract, or 40% lime extract are effective in changing saliva pH to become more alkaline and prevent against dental caries.Material and Methods: This study used purposive sampling with pretest/post-test control group design. The total sample group included 120 children who fulfilled the criteria. The control group, containing 30 children, was rinsed with distilled water while 90 children were divided into 3 intervention groups containing 30 children each. Each intervention group was treated with either a solution of 12.5% cocoa seed extract, a solution of 30% green tea catechins extract or a solution of 40% lime extract.Results: Using the Friedman Test, rinsing with distilled had no significant effect in changing the pH of saliva into normal alkaline conditions and preventing against dental caries. Significant changes the pH of saliva was found with 12.5% cocoa seed extract after the first 15 minutes resulting in alkaline or normal conditions for prevention of dental caries.Conclusion: The mouthwash solution containing 12.5% cocoa seed extract is most effective to change the pH of the saliva into alkaline and normal state in preventing dental caries.